2015
DOI: 10.1061/jswbay.0000800
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Denitrification in Bioretention Using Woodchips as an Organic Carbon Source

Abstract: Bioretention systems fundamentally lack the ability to effectively reduce total nitrogen concentrations from urban stormwater. Column tests were conducted to simulate a bioretention anoxic zone and evaluate the effects of stormwater retention time, limestone addition, and woodchip species, size, and mass percentage on the bioretention denitrification process. Denitrification of an artificial stormwater was demonstrated and appeared to follow first-order kinetics. A 0.8-day average retention time showed the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 32 publications
3
44
0
Order By: Relevance
“…This indicates that different processes control TKN and DOC release from the wood chips or biofilm. Similar results were observed by Schmidt and Clark (2012) who observed no correlation between TKN and DOC in a denitrification wall for wastewater treatment; however, Peterson et al, (2015) observed similar trends between TKN and DOC in a denitrifying biofilter that was evaluated under alternating saturated and unsaturated conditions.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This indicates that different processes control TKN and DOC release from the wood chips or biofilm. Similar results were observed by Schmidt and Clark (2012) who observed no correlation between TKN and DOC in a denitrification wall for wastewater treatment; however, Peterson et al, (2015) observed similar trends between TKN and DOC in a denitrifying biofilter that was evaluated under alternating saturated and unsaturated conditions.…”
Section: Discussionsupporting
confidence: 88%
“…3a). Based on these data alone, an increase in detention time will increase NO 3 -removal as was previously observed by others (Kim et al, 2003;Smith, 2008;Lucas and Greenway 2011;Peterson et al, 2015). However, mixing of the influent and pore water may also affect effluent NO 3 -concentrations (Kim et al, 2003) (Fig.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…However, denitrification or nitrification is not likely to occur significantly within the short-time (around 1 h) wetting period [36], but should mainly occur during the ADPs. The introduction of an SZ with stored runoff could pose little effect on nitrification (mostly aerobic process) but significantly affect denitrification by facilitating the growth of anaerobic denitrifiers to promote the removal of NO 3 − during the ADPs [20,34,[36][37][38]. This can explain the growing NO 3 − removal efficiencies with the increasing SZ depths (Figure 6), which can be strongly supported by the significant difference of ANOVA analysis (p < 0.05 for NO 3 − ).…”
Section: Nomentioning
confidence: 99%